Challenges in Conducting us Digital Diplomacy in Central Asia (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
General Background: Digital diplomacy has become an essential instrument in international relations, particularly for global powers seeking to strengthen their influence through technological means. The United States actively employs digital diplomacy to advance its foreign policy goals, including in strategically significant regions such as Central Asia.Specific Background: Despite possessing advanced digital capabilities, the U.S. faces significant obstacles in implementing its digital diplomacy in Central Asia. Political restrictions, regulatory challenges, and the dominance of Russian and Chinese digital infrastructures hinder U.S. efforts. Governments in the region frequently restrict internet access and social media platforms, citing national security concerns, which further complicates diplomatic engagement.Knowledge Gap: Existing studies have analyzed U.S. digital diplomacy broadly but have not sufficiently examined its effectiveness in regions with restrictive internet governance and competing geopolitical interests. There is limited research on the specific challenges faced by U.S. digital diplomacy in Central Asia’s complex political and media landscape.Aims: This study aims to identify the key barriers to U.S. digital diplomacy in Central Asia and evaluate its effectiveness in overcoming these challenges.Results: The findings indicate that regional governments impose strict internet regulations to control information flows, limiting external digital influence. The study also reveals that public reliance on Russian media further reduces the impact of U.S. digital diplomacy.Novelty: This study provides a focused analysis of U.S. digital diplomacy in Central Asia, highlighting the interplay between state control, foreign influence, and digital engagement strategies.Implications: For U.S. digital diplomacy to be effective, it must adapt to regional constraints by fostering local partnerships, respecting national regulations, and providing viable digital alternatives to existing information networks.